(Invited) Challenges on Surface Conditioning in 3D Device Architectures: Triple-Gate FinFETs, Gate-All-Around Lateral and Vertical Nanowire FETs. (15th August 2017) - Veloso, Anabela; Paraschiv, Vasile; Vecchio, Emma; Devriendt, Katia; Li, Waikin; Simoen, Eddy; Chan, B. T.; Tao, Zheng; Rosseel, Erik; Loo, Roger; Milenin, Alexey P.; Kunert, Bernardette; et al.
Abstract : This work reports on some key integration aspects for 3D devices fabrication, focusing first on the impact of thermal and plasma treatments at gate module for triple-gate finFETs and their ultimate scaling limit: gate-all-around (GAA) nanowire (NW) FETs, which can be implemented in a lateral (with one or more lateral wires vertically stacked) or vertical configuration. The selected doping schemes and gate metals can also be powerful knobs to engineer the interface properties. In addition, specific steps for lateral NWFETs, such as the wires release process, will be addressed here. Vertical NWFETs, corresponding to the move from a 2D to a 3D CMOS layout, have the potential for lower parasitics, reduced power consumption and for enabling smaller, higher performing SRAM bitcells. We will present here alternative, novel approaches for building and characterizing these devices, focusing on channel-first schemes with improved process control, while tackling critical etch-layout dependences.